KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD BERDASARKAN TES INTERNASIONAL DAN TES LOKAL - Imam Agus Basuki Basuki (Fakultas Sastra Universitas Negeri Malang, 2011)
This article is aimed at elaborating not only the students’ reading comprehension based on international test and local test conducted for elementary school students, grade four but also the corelation of both results. This descriptive research was conducted at 12 elementary schools at 5 provinces located in Java and Sumatra. The instruments used for reading comprehension test were PIRLS, an international test and the researcher-made test. The result of the study shows that the fourth graders’ ability in comprehending the texts is very low. They could only understand 30% of the reading texts, both informative and literary texts. The result of the international tests have a very high corelation with the result of the researcher- made test, though it shows lower result than the result of local tests.